Continuous hydrogen and butyric acid fermentation by immobilized Clostridium tyrobutyricum ATCC 25755: Effects of the glucose concentration and hydraulic retention time - Mitchell, Robert J.; Kim, Ji-Seong; Jeon, Byung-Seung; Sang, Byoung-In (ELSEVIER SCI LTD, 2009)
The effects of the hydraulic retention time (HRT = 8, 10, 12 or 16.7 h) and glucose concentration (30, 40 or 50 g/L) on the production of hydrogen and butyrate by an immobilized Clostridium tyrobutyricum culture, grown under continuous culturing conditions, were evaluated. With 30 g/L glucose, the higher HRTs tested led to greater butyrate concentrations in the culture, i.e., 9.3 g/L versus 12.9 g/L with HRTs of 8 h and 16.7 h, respectively. In contrast, higher biogas and hydrogen production rates were generally seen when the HRT was lower. Experiments with different glucose concentrations saw a significant amount of glucose washed out when 50 g/L was used, the highest being 22.7 g/L when the HRT was 16.7 h. This study found the best conditions for the continuous production of hydrogen and butyric acid by C. tyrobutyricum to be with an HRT of 12 h and a glucose concentration of 50 g/L, respectively. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: BIOHYDROGEN PRODUCTION; DELETED MUTANT; CONSTRUCTION